Patterns of persistent genital human papillomavirus infection among women worldwide: A literature review and meta‐analysis. Issue 6 (11th October 2012) - Rositch, Anne F.; Koshiol, Jill; Hudgens, Michael G.; Razzaghi, Hilda; Backes, Danielle M.; Pimenta, Jeanne M.; Franco, Eduardo L.; Poole, Charles; Smith, Jennifer S.
<x xml:space="preserve">Abstract</x> Persistent high‐risk human papillomavirus (HR‐HPV) infection is the strongest risk factor for high‐grade cervical precancer. We performed a systematic review and meta‐analysis of HPV persistence patterns worldwide. Medline and ISI Web of Science were searched through January 1, 2010 for articles estimating HPV persistence or duration of detection. Descriptive and meta‐regression techniques were used to summarize variability and the influence of study definitions and characteristics on duration and persistence of cervical HPV infections in women. Among 86 studies providing data on over 100, 000 women, 73% defined persistence as HPV positivity at a minimum of two time points. Persistence varied notably across studies and was largely mediated by study region and HPV type, with HPV‐16, 31, 33 and 52 being most persistent. Weighted median duration of any‐HPV detection was 9.8 months. HR‐HPV (9.3 months) persisted longer than low‐risk HPV (8.4 months), and HPV‐16 (12.4 months) persisted longer than HPV‐18 (9.8 months). Among populations of HPV‐positive women with normal cytology, the median duration of any‐HPV detection was 11.5 and HR‐HPV detection was 10.9 months. In conclusion, we estimated that approximately half of HPV infections persist past 6 to 12 months. Repeat HPV testing at 12‐month intervals could identify women at increased risk of high‐grade cervical precancer due to persistent HPV infections.